Regionalni razvoj včeraj, danes, jutri - Polajnar Horvat, Katarina; Nared, Janez; Razpotnik Visković, Nika (Regionalni razvoj, 2021)
The celebration of the 50th anniversary of regional policy in Slovenia and the 30th anniversary of the country's independence is an opportunity to assess the efforts made so far in promoting regional development as well as to look to the future. In the book, we look at the path taken, describe the system of promoting regional development in the past, and point to the success of regional policy in eliminating interregional disparities. We present the role of regional development agencies and regional spatial planning in regional development and the quality of life in border problem areas from the perspective of the people living there. In the final part, we focus on future development. We point out the role of digitalisation and demographic change and try to shed light on future developments also from a philosophical perspective. Demographic, climate, economic and social changes require new approaches, fresh ideas and, above all, a systematic identification of development guidelines, ideas, development opportunities and factors that, taken together, can lead to a more balanced development of the country in all areas. Harmonious development is everyone's responsibility, but we can only achieve it together.